2015
DOI: 10.3906/kim-1403-44
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and evaluation of antioxidant activities of novel 1,3,4-oxadiazole and imine containing 1$H$-benzimidazoles

Abstract: Some novel 2-(substitutedbenzylthio)-5-((2-(4-substitutedphenyl)-1 H -benzo[d]imidazol-1-yl)methyl)-1,3,4oxadiazoles (5-12) and 2-(2-(4-chlorophenyl)-1 H -benzo[d]imidazol-1-yl)-N ′ -(arylmethylene)acetohydrazide derivatives (13-22) were prepared and their in vitro antioxidant properties were investigated by determination of rat liver microsomal NADPH-dependent inhibition of lipid peroxidation (LP) levels and microsomal ethoxyresorufin O-deethylase (EROD)activity. Compound 18 was found to be the most active co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…Synthesis of the target compounds 2a–2o is outlined in Scheme 1 . Initially, 1,2-phenylenediamine was reacted with various sodium bisulfite adducts of aldehydes under microwave irradiation conditions to obtain the previously reported 2-(4-substitutedphenyl)-1 H -benzimidazoles 1a–1o [ 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ]. In the second step, compounds 1a–1o were treated with 2-(morpholin-4-yl)ethyl chloride in the presence of NaH, and subjected to microwave irradiation again.…”
Section: Resultsmentioning
confidence: 99%
“…Synthesis of the target compounds 2a–2o is outlined in Scheme 1 . Initially, 1,2-phenylenediamine was reacted with various sodium bisulfite adducts of aldehydes under microwave irradiation conditions to obtain the previously reported 2-(4-substitutedphenyl)-1 H -benzimidazoles 1a–1o [ 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ]. In the second step, compounds 1a–1o were treated with 2-(morpholin-4-yl)ethyl chloride in the presence of NaH, and subjected to microwave irradiation again.…”
Section: Resultsmentioning
confidence: 99%
“…In our previous studies, we described the synthesis and antioxidant effects of 2-[2-(4chlorophenyl)benzimidazole-1-yl]-N-(2-arylmethylene amino) acetamides on EROD activity and LPO levels. 21,33 When compared with the results obtained from these studies, benzimidazoles carrying 4-chloro phenyl ring at the second position were found to be more effective than benzimidazole counterpart carrying non-substituted phenyl rings for both assays.…”
Section: Results Discussion and Conclusionmentioning
confidence: 99%
“…The synthesis of target hydrazones ( 5a‐b ) was achieved through reaction sequence outlined in Scheme‐1. 1 H‐ benzimidazoles ( 3a‐b ) were prepared by oxidative condensation of appropriate aldehyde ( 2a‐b ) with o ‐phenylenediamine and sodium metabisulfite . Compounds ( 3a‐b ) were reacted with ethyl bromoacetate in KOH/DMSO to furnish the N‐substituted esters which on subsequent treatment with hydrazine hydrate under reflux in ethanol gave the respective hydrazides ( 4a‐b ).…”
Section: Methodsmentioning
confidence: 99%